Bringing Territorialicy to EU Cohesion Policy via the Territorial Agenda 2030 - Medeiros, E. (Seminar on Territorial Agenda 2030.Territorial Values and specificities in the European recovery plan and cohesion policy, 2021)
• Good morning. First of all, I would like to thank the invitation made by Professor Joaquin Farinos to make a presentation on this very interesting and relevant topic which is the TA 2030 • As you can see from the title of my presentation, I will focus it on the potential links between the TA 2030 and EU Cohesion Policy. • As a Geographer I systematically notice how the territorial dimension of polices if widely misunderstood, not only by policymakers, but also within the academic meanders. • In essence, this territorial dimension should be analysed not only by the policies strategic goals which should focus on territorial development and cohesion rather than only economy growth, but also on their potential territorial impacts (generically meaning the main socioeconomic, governance, environmental sustainability, and spatial planning related impacts). And finally, policies should target different territorial levels. • In sum, the degree of territorialisation of policies depends a strong territorial intervention strategy focused on development and cohesion, on high levels of expected territorial impacts (meaning in all dimensions of territorial development), and on its operational capacity on all territorial scales. • This increased territorial policy approaches should touch the territorial universe of territorialicy understood as a process of incorporating a territorial driven policy design. • Here we not only see crucial and known policy goals such as Territorial Development and Territorial Cohesion, but also others such as the valorisation of the Territorial Capital, the promotion of Territorial Governance, Territorial Cooperation, Territorial Planning and Territorial Integration, but also the implementation of Territorial Impact Assessment processes, at several stages: ex-ante, mid-term and ex-post. • So where does EU Cohesion Policy enters in this territorialicy policy approach which links to the implementation of the TA 2030? • As recently concluded in an Opendays 2030 workshop on the TA 2030, this Agenda does not have a budget of its own. So, one possible source of funding to implement its proposed strategy could be via EU Cohesion Policy funding. In that mentioned event, the Portuguese minister for territorial cohesion stated that around 30% of the post-2020 EU Cohesion Funds are due to be allocated on implementing the TA 2030 goals. In particular on environmental related policies. • Indeed, if one related the main pillars of the territorial universe and the five main objectives for EU investments post-2020, one can see a sea of possibilities in all of them. For instance, spatial planning processes could be financially supported via the Connected Europe goal, and Territorial Cooperation processes via the Europe closer to citizens goal. • In a broader approach, I suggest the use of EU Cohesion Policy funds in five specific policy goals: • 1 - Favouring the concentration of funding in medium cities/functional regions in less developed territories: As several studies have showed, despite the positive impacts of EU Cohesion Policy related investments in supporting territorial development processes in basically all EU regions, they did not invert territorial exclusion processes at the national level. In other words, the concentration of EU funding in all regions did not led to achieving the desired EU territorial cohesion goal at the national level. In this context, I suggest the concentration of these EU investments in what I call ‘territorial cohesion cities’, (see the example for Iberian Peninsula), to act as regional development anchors in EU less development regions. • 2 - Ring-fencing innovation funding to promoting circular economy and renewable energy production: Taking the case of Iberia Peninsula, the solar energy potential is vast and, in many areas (such as the south of Portugal) it is still largely untapped, despite positive recent trends in installing solar photovoltaic facilities. These, however, in our view, should be mostly implemented in urban areas with high levels of solar exposure (see Lisbon as an Example). • 3 - Promoting cross-border integration via the implementation of cross-border planning strategies: One of the most positive EU policies related stories has been the positive impacts of Territorial Cooperation processes (cross-border and transnational), in particular in reducing border obstacles thus promoting territorial integration across Europe. Here, the next step, in our view, is to go from cross-border and transnational cooperation into cross-border and transnational planning, both at the regional and local levels, by taking stock on existing institutional arrangements at the regional (EGTCs + Euroregions) and local (Eurocities) levels. • But these cross-border planning processes should only encompass the border area, and not the full scope of the border NUT2 to be more effective – See presentation. • 4 - Following a wider transnational planning approach in particular by improving physical connections: For instance, it is hard to plan a functional high-speed railway system in Portugal without taking into consideration the one being implemented in Spain. • 5 - Financially reinforce sustainable urban integrated development strategies SUDS: There are currently more than 700 SUDS, 108 in Portugal alone. Many are still being implemented but the first evaluations have seen positive impacts in the physical, socioeconomic and environmental rehabilitation of some deprived neighbourhoods in some cities. However, just like it happened with the implementation of the EU URBAN initiative, the limited funding of the SUDS, in view of the needs of these deprived urban neighbourhoods, can only contribute, in many cases, to mitigate urban development and planning needs. Hence the need to increase the channelling of funding to these strategies.